2020
DOI: 10.21076/vizyoner.650683
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflation on Firm Profitability: An Application in Retail Sector of Borsa Istanbul

Abstract: The cost of sales increases together with an increase in inflation. The firms that aims to reach a profit target, reflect the cost increases on prices. Increases in prices may be higher than those in costs. Increasing prices lead to inflation. The firms in Turkey experienced a sudden increase in the exchange rates in the period of July-September 2018, and used this depreciation as an excuse for increasing their prices. However, even those firms that were slightly affected by the increase in the exchange rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Correlation analysis, t-tests, and financial analysis were conducted on various factors, including revenues, cost of sales, gross profits, operating profits, and net profits. The findings revealed that supermarkets increased their selling prices at a higher rate compared to the cost of sales (Dayı, 2020).…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Correlation analysis, t-tests, and financial analysis were conducted on various factors, including revenues, cost of sales, gross profits, operating profits, and net profits. The findings revealed that supermarkets increased their selling prices at a higher rate compared to the cost of sales (Dayı, 2020).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Furthermore, the study highlighted that the results obtained through the TOPSIS method differed from those obtained through the return on assets ratio analysis (Satır, Kısakürek, & Yaşar, 2020). Dayı (2020) presents the argument that inflation leads to an increase in sales costs. Companies respond to these cost increases by adjusting prices to achieve their target profits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, BPS will monitor price developments for these goods and services on a monthly basis in several cities, in traditional and modern markets for several types of goods/services in each city. As a result of inflation that continues to increase and the increase is uncontrollable, it affects all sectors of the economy [7], [8]. Particularly in the capital market, stock prices fluctuated greatly, as did the stock price index of industrial sectors on the Indonesia Stock Exchange.…”
Section: Introductionmentioning
confidence: 99%